Health inequalities in cause-specific mortality in Costa Rica: a population-based cohort study - Fantin, Romain; Delpierre, Cyrille; Barboza-Solís, Cristina (Revista de Saúde Pública, 2023)
OBJECTIVE: To analyze health inequalities in cause-specific mortality in Costa Rica from 2010 to 2018, observing the main causes for inequality in the country. METHODS: The National Electoral Rolls were used to follow-up all Costa Rican adults aged 20 years or older from 2010 to 2018 (n = 2,739,733) in an ecological study. A parametric survival model based on the Gompertz distribution was performed and the event death was classified according to the ICD-10. RESULTS: After adjustment for urbanicity, the poorest districts had a higher mortality than the wealthier districts for most causes of death except neoplasms, mental and behavioral disorders, and diseases of the nervous system. Urban districts showed significantly higher mortality than mixed and rural districts after adjustment for wealth for most causes except mental and behavioral disorders, diseases of the nervous system, and diseases of the respiratory system. Differences according to wealth were more frequent in women than men, whereas differences according to urbanicity were more frequent in men than in women. CONCLUSIONS: The study’s findings were consistent, but not fully similar, to the international literature.